Contezolid, a novel oxazolidinone antibiotic, may improve drug-related thrombocytopenia in clinical antibacterial treatment - Li, Bi; Liu, Ying; Luo, Jiaqi; Cai, Yun; Chen, Mengli; Wang, Tianlin (Frontiers in Pharmacology, 2023)
One of the major limitations of existing oxazolidinone antibiotics for clinical application is their characteristic adverse reactions, especially thrombocytopenia. In anti-infective treatment, when patients suspected of having drug-induced thrombocytopenia, immediate discontinuation of the drugs responsible always be carried out as initial step. Even if it is patients with severe infection, may need to change antibacterial drugs or even discontinue antibacterial treatment, because thrombocytopenia may bring more serious clinical adverse prognosis. In addition, if the patient needs to continue antibacterial treatment after discharge, the lack of conditions for monitoring the platelet level may also bring hidden dangers to the patient. Contezolid is an orally administered oxazolidinone antibacterial agent approved by the National Medical Products Administration of China in 2021. We found that, contezolid may had an improved safety profile with a significantly reduced potential for myelosuppression. This conclusion has obtained some clues in our clinical observational study. In this article, we reviewed the advantages of contezolid as a new oxazolidinone antibiotic and described three typical cases in clinical with drug-induced thrombocytopenia after using linezolid. Although in different situations, the platelet levels of these patients were all significantly improved with varying degrees after the adaptation of contezolid.